Molecular mechanisms and clinical implications of multiple forms of mitophagy in the heart. Issue 14 (17th December 2020) - Saito, Toshiro; Hamano, Kimikazu; Sadoshima, Junichi
Abstract: Mitochondria, the primary ATP-producing organelles, are highly abundant in cardiomyocytes. Mitochondrial function readily deteriorates in the presence of stress and, thus, maintenance of mitochondrial quality is essential for sustaining pump function in the heart. Cardiomyocytes under stress attempt to maintain mitochondrial quality primarily through dynamic changes in their morphology, namely fission and fusion, degradation, and biogenesis. Mitophagy, a mitochondria-specific form of autophagy, is a major mechanism of degradation. The level of mitophagy is altered in stress conditions, which, in turn, significantly affects mitochondrial function, cardiomyocyte survival, and death and cardiac function. Thus, mitophagy has been emerging as a promising target for treatment of cardiac conditions. To develop specific interventions, modulating the activity of mitophagy in the heart, understanding how mitochondria are degraded in a given condition is important. Increasing lines of evidence suggest that there are multiple mechanisms by which mitochondria are degraded through mitophagy in the heart. For example, in addition to the well-established mechanism commonly utilized by general autophagy, involving Atg7 and LC3, recent evidence suggests that an alternative mechanism, independent of Atg7 and LC3, also mediates mitophagy in the heart. Here, we describe molecular mechanisms through which mitochondria are degraded in the heart and discuss their functional significance. We also discuss molecular interventions to modulate the activity of mitophagy and their potential applications for cardiac conditions. Graphical Abstract: